Good governance in Sub-Saharan Africa: opportunities and lessons - Newiak, Monique; Segura-Ubiergo, Alex; Wane, Abdoul Aziz (Washington, D.C International Monetary Fund (IMF), 2022)
Governance and corruption issues have taken the center stage in international discussions, especially after the adoption by the IMF in 2018 of a new framework for engagement on governance and corruption. Sound institutions that guarantee integrity in the management of public affairs are critical on the path toward higher and more inclusive growth. Corruption undermines the quality of institutions, weakens the effectiveness of government programs, and compromises social trust in government policies. Indeed, countries around the world that improved their governance systems are reaping a “governance dividend,” and governance-enhancing reformist countries in sub-Saharan Africa include Botswana, Rwanda, and Seychelles. In addition, Liberia, Sierra Leone, and Angola demonstrate that important reforms are possible, including in fragile environments. The importance of good governance has acquired even more importance as countries try to introduce policies to fight the ongoing COVID-19 pandemic. Special attention to governance in an emergency context, including situations associated with conflict, other health crises and natural disasters, is therefore essential. Innovation and new technologies are critical instruments that policymakers can use in their efforts to improve governance and transparency. (IMF page)
Introduction: reaping the dividends of good governance -- 1 The Macro-fiscal benefits of eliminating corruption In Government -- 2 Pathways to reaping a governance dividend in Sub-Saharan Africa -- 3 Three Strong governance performers in Sub-Saharan Africa: achievements and way forward -- 4 Reaping the benefits from better governance in Nigeria -- 5 CEMAC: A regional approach to enhancing governance -- 6 Macro-fiscal gains from anticorruption reforms in the republic of Congo -- 7 Addressing corruption in fragile country settings -- 8 Reaping the benefits of good governance in the democratic republic of Congo -- 9 Madagascar: institution-building in a Fragile State -- 10 Strengthening governance and reducing vulnerability to corruption in Comoros -- 11 Accountability in supporting the emergency response to a crisis: lessons from COVID-19 funds -- 12 The Role of supreme audit institutions in addressing corruption, including in emergency settings -- 13 Central Bank governance in Sub-Saharan Africa: an overview based on experience with the IMF’s Safeguards assessments -- 14 The Dividends of digitalization and big data to institutional quality and the macroeconomy -- 15 Digitalization, corruption, and trust in tax officials in Africa
Includes bibliographical references and index.
Keywords: Corruption; POLITICAL CORRUPTION; CORRUPTION; Africa, Sub Saharan